2015
DOI: 10.1111/1365-2745.12456
|View full text |Cite
|
Sign up to set email alerts
|

Do native and invasive plants differ in their interactions with arbuscular mycorrhizal fungi? A meta‐analysis

Abstract: Summary1. Divergent hypotheses have been proposed that suggest plant invasions either enhance or degrade the mutualism between plants and arbuscular mycorrhizal (AM) fungi, but their relative support remains unknown. 2. We conducted a meta-analysis using 67 publications, involving 70 native and 55 invasive plant species to assess support for the enhanced mutualism hypothesis, the degraded mutualism hypothesis and an alternative hypothesis that factors other than invasive status (such as plant functional group)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
162
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(185 citation statements)
references
References 73 publications
15
162
7
1
Order By: Relevance
“…Consequently, root addition may have had stronger negative effects on forb growth in the conditioning phase, and may have led to a stronger decrease in forb biomass in home soil than in foreign soil in the feedback phase. Although forbs generally benefit more from AMF than grasses (Hoeksema et al, 2010;Bunn et al, 2015), in some grass-dominated systems, like ours, the opposite pattern is observed (Wilson & Hartnett, 1997;McCain et al, 2011). As a result, forbs may benefit less from the presence of AMF in grassland systems, resulting in stronger negative PSF effects.…”
Section: Responses Of Grasses Vs Forbsmentioning
confidence: 50%
“…Consequently, root addition may have had stronger negative effects on forb growth in the conditioning phase, and may have led to a stronger decrease in forb biomass in home soil than in foreign soil in the feedback phase. Although forbs generally benefit more from AMF than grasses (Hoeksema et al, 2010;Bunn et al, 2015), in some grass-dominated systems, like ours, the opposite pattern is observed (Wilson & Hartnett, 1997;McCain et al, 2011). As a result, forbs may benefit less from the presence of AMF in grassland systems, resulting in stronger negative PSF effects.…”
Section: Responses Of Grasses Vs Forbsmentioning
confidence: 50%
“…These growth strategies may facilitate more beneficial mycorrhizal associations in T. ceratophorum, especially when [CO 2 ] limits plant growth. A recent meta-analysis further shows that mycorrhizal responses are often dampened in invasive plant species (Bunn et al, 2015). Furthermore, the positive relationship between fungal colonization and plant size that is often observed for native hosts is generally absent in invasive hosts.…”
Section: Host-specific Differences In Mycorrhizal Functioningmentioning
confidence: 98%
“…This does not support the divergent hypothesis that states plant invasion either promote or decrease the mutualistic association between plants and AM fungi. Though the abundance of AM fungi in both, native and invasive plant species did not differ, the AM colonization was lower in the native plant species when compared with invasive ones (Bunn et al, 2015).…”
Section: Role Of Mycorrhizal Symbiosis In Plant Invasionmentioning
confidence: 76%